Evaluate educational aspects of student conduct processes. Issue 8 (December 2014) - Bennett, Laura
<x xml:space="preserve">Abstract</x> Campus officials throughout the country are revising policies, procedures and training for those who handle reports of sexual misconduct, including sexual violence. It all comes in response to efforts to comply with the Violence Against Women Act, the April 2011 "Dear Colleague Letter, " and Office for Civil Rights Investigations.